Environmental regulation and environmental equality: the role of green finance and the digital economy - Chen, Ziyi; Zhuang, Guoya; Li, Feifei (Frontiers in Environmental Science, 2024)
IntroductionEnvironmental issues are related to the physical health and welfare level of all human beings, and the mandatory and dominant nature of environmental regulation (ER) effectively solves the difficult problem of unequal environmental obligations and gives impetus to improving environmental equality.MethodsTherefore, based on a sample of 238 prefecture-level cities in China between 2011 and 2020, this paper empirically examines the mechanism and effect of ER intensity on environmental fairness using the Gini coefficient and the Theil index. In addition, this paper further tests the mechanisms of mediating influence and moderating effect of ER on environmental equality.ResultsThe results of the study found that (1) On the basis of mitigating endogenous problems such as adopting instrumental variable strategies, the increase in the intensity of ER has a significant contribution to the realization of environmental equality. (2) ER contributes to the realization of environmental equality through the green innovation transformation effect, which is more pronounced in innovative regions. (3) The level of development of green finance and the digital economy, as an important instrumental approach to promoting sustainable development, can strengthen the path of environmental policy to mitigate environmental inequality.DiscussionThis paper provides suggestions and insights for promoting the implementation of government environmental policies, enhancing the digital transformation of economic development, and promoting the construction of a society-wide green equality system.